MENGHADIRKAN TASAWUF DI TENGAH PLURALISME DAN ANCAMAN RADIKALISME - Danial, Danial (Analisis: Jurnal Studi Keislaman, 2011)
The phenomena of violence, terrorism, and interreligious conflict evolving some of  hard line muslims (radical) reveals critical question whether Islam is a real religion that is rah}matan lil‘a>lami>n. The flowing of hesitation of International society, the propaganda of mass media, and the tendentious accusation is pointed to Islam and muslims. To respond it, it is needed to read a new reading for Islam and to delve into its sources of  teachings in the view of  modest mysticism, smooth, love of peace, and anti-violence.